2019
DOI: 10.1111/labr.12167
|View full text |Cite
|
Sign up to set email alerts
|

Tattoos, Lifestyle, and the Labor Market

Abstract: In this study, we look at the factors determining the decision to get a tattoo and relate this to several outcome measures, such as income, employment status, and health. The analyses are based on unique panel data of a representative sample of Dutch individuals. The tattooed population differs significantly from the non-tattooed population on a wide range of characteristics. We use fixed effects and instrumental variable analysis to explore the effects of tattoos. Our analyses suggest less favorable outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 23 publications
2
19
1
1
Order By: Relevance
“…The focus of this research is to build upon this prior knowledge as to the impact that facial tattoos may have on the employment screening process. Dillingh, Kooreman, and Potters (2016) research observed that 10% of the participants had tattoos on the face and neck area of the body.The decision to have a tattoo placed on the face or neck area has been shown to have a negative economic and social consequence for the individual. Brallier, Maguire, Smith,& Palm (2011) suggested that people in a managerial capacity and the greater parts of society feel that a visible tattoo (Arndt, McCombs, Tolle, & Cox, 2017) remains a factor in determining suitability for employment.…”
Section: Tattoo Locationmentioning
confidence: 99%
“…The focus of this research is to build upon this prior knowledge as to the impact that facial tattoos may have on the employment screening process. Dillingh, Kooreman, and Potters (2016) research observed that 10% of the participants had tattoos on the face and neck area of the body.The decision to have a tattoo placed on the face or neck area has been shown to have a negative economic and social consequence for the individual. Brallier, Maguire, Smith,& Palm (2011) suggested that people in a managerial capacity and the greater parts of society feel that a visible tattoo (Arndt, McCombs, Tolle, & Cox, 2017) remains a factor in determining suitability for employment.…”
Section: Tattoo Locationmentioning
confidence: 99%
“…The quantitative survey investigations have provided the strongest evidence that being tattooed does not have a detrimental impact on individuals. While Dillingh et al (2016) found that being tattooed had a negative influence on being employed, there was no impact on annual earnings, among a representative national sample of Dutch adults. In addition, French et al (2016) found that tattooed employees in national samples of young people employed in the USA and Australia did not earn less annually once human capital (e.g.…”
Section: Previous Research On Tattoos and Workplace Prejudice And Discriminationmentioning
confidence: 75%
“…On one hand, a variety of studies have signaled that individuals with tattoos are viewed as less acceptable for the workplace and perceived as lower performers compared to those without body art (Baumann et al , 2016; Brallier et al , 2011; Henle et al , 2018; Miller et al , 2009; Timming, 2015; Timming et al , 2017). On the other hand, research also has provided evidence that those with tattoos are not likely to be penalized (Dillingh et al , 2016; French et al , 2016; French et al , 2019). Such conflicting research findings necessitate further examining the degree to which tattooed employees receive unfavorable workplace treatment.…”
mentioning
confidence: 99%
“…As the U.S. has become “a tattooed nation,” individuals with tattoos report that they rarely experience negative encounters or blatant discrimination due to their tattoos . For example, after controlling for numerous demographic and socioeconomic characteristics, having a tattoo is not associated with lower employment probability or labor market earnings . Although statistically significant differences in aggression and rebelliousness exist, these effects are quite small and have diminished over time and will likely continue to do so .…”
Section: Introductionmentioning
confidence: 99%